Social attributes aware data forwarding strategy in intermittently connected wireless networks - UDa-peng W; ONGXiao-long K; HANGHong-pei Z; IUQiao-shou L; IONGYu X; ANGRu-yan W (Tongxin xuebao)
The nodes in the intermittent connection wireless network have the aggregation feature,the relation between nodes should be considered by the packet transmitting procedure.A social attributes aware data forwarding strategy in ICWN is proposed.According to the multiple parameters of network status,the social attribute of nodes is evaluated with the distribute manner; moreover,the relation between nodes is determined.Consequently,the packets are forwarded to their destination nodes.Results show that the packet delivery ratio and the delay can be optimized by proposed strategy.